Head and Neck Reconstruction: Does Surgical Specialty Affect Complication Rates? - Drinane, James J.; Drinane, John; Nair, Lakshmi; Patel, Ashit (Journal of Reconstructive Microsurgery, 2019)
Background Reconstruction of head and neck defects resulting from resection of head and neck masses is performed by both plastic surgeons and otolaryngologists. The American College of Surgeons National Surgical Quality Improvement (NSQIP) database allows one to directly compare the outcomes for a given procedure based upon specialty. The purpose of this study is to compare outcomes and resource utilization of microvascular head and neck reconstruction between plastic surgery and otolaryngology.Methods Institutional review board approval was obtained and NSQIP was queried from 2005 to 2015 with inclusion of Current Procedural Terminology codes for free tissue transfer performed for head and neck reconstruction. Outcomes were compared between cases having otolaryngology and plastic surgery as performing the free flap reconstruction.Results During 2005 to 2015, a total of 2,322 flaps were performed, 893 by plastic surgery and 1,429 by otolaryngology. Average length of stay (LOS) was 13.7 and 11.4 days for plastic surgery and otolaryngology, respectively. It was found that plastic surgery performed more osteocutaneous flaps than otolaryngology. Higher rates of superficial surgical site infection, deep surgical site infections, wound dehiscence, myocardial infarction, bleeding complications, sepsis, unplanned return to the operating room, and unplanned readmission were observed for patients treated by otolaryngology (p < 0.05).Conclusion This study shows plastic surgery patients have superior outcomes with regards to free tissue transfers of the head and neck when compared with otolaryngology patients. Although plastic surgery patients experienced a longer LOS, the significantly lower complication rate supports an overall more optimal resource utilization. Future studies may elucidate potential cost savings in patients treated by plastic surgery.
Keywords: head and neck reconstruction; microsurgery; otolaryngology; plastic surgery